If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(7x + 10) = 8x + 5 Reorder the terms: -1(10 + 7x) = 8x + 5 (10 * -1 + 7x * -1) = 8x + 5 (-10 + -7x) = 8x + 5 Reorder the terms: -10 + -7x = 5 + 8x Solving -10 + -7x = 5 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. -10 + -7x + -8x = 5 + 8x + -8x Combine like terms: -7x + -8x = -15x -10 + -15x = 5 + 8x + -8x Combine like terms: 8x + -8x = 0 -10 + -15x = 5 + 0 -10 + -15x = 5 Add '10' to each side of the equation. -10 + 10 + -15x = 5 + 10 Combine like terms: -10 + 10 = 0 0 + -15x = 5 + 10 -15x = 5 + 10 Combine like terms: 5 + 10 = 15 -15x = 15 Divide each side by '-15'. x = -1 Simplifying x = -1
| 5(n+4)-(9n-3)=-5n | | 3x+4x+15=4x-9 | | 8s^2-50=0 | | (x-7)2=4 | | 4(90-x)=180-x | | 12c^2-17cd-5d^2=0 | | 5x-22=8 | | 27=3(2x+1) | | 8+6=2x | | M=nx | | 4x-30=x+15 | | 10r^3+44r^2-30r=0 | | 4x-7=-3x+14 | | 5+1.6x=1 | | 10u^2-29u+10=0 | | x+3y=-9 | | 3(9-x)=5+x | | 7x-4=3(3+x)-1 | | 11x-5(3x+2)=14x+62 | | -8x+4y=24 | | 4(x+2)=-2(x-1) | | 3x+18=0 | | 3(5c-1)-2=12c+4 | | -x-8=2x+7 | | 2x-16=6(x-2) | | 2x=5x+12 | | 18a=b | | 4x+14=7x-4 | | 4n+8=26-2n | | 44-12=4(x-7) | | 35+3y-5=12y-12-3y | | 3(x-2)=5(x+2) |